Investigation of mechanical properties of auxetic woven polymer composite material: Untersuchung der mechanischen Eigenschaften von auxetisch gewebten Polymer‐Verbundwerkstoffen. Issue 2 (20th February 2018) - Hussain, M.; Nawab, Y.; Rizwan, Z.; Mumtaz, A.; Basit, A.
Abstract: Contrary to normal materials, the auxetic/meta‐materials expand transversally as well as longitudinally when subjected to longitudinal load and contract in both directions on compression. In this work, auxeticity is obtained in composites reinforced with carbon woven fabrics placed at certain angles. The auxetic effect on the mechanical properties of the prepared carbon/epoxy composites was investigated. The mechanical properties include the tensile, flexural and impact properties. It is found that the tensile properties are not affected by the auxetic effect; however, the flexural and impact properties are significantly enhanced by the auxetic effect.